Urban land, real estate, and subdivisions the historical suburbanization of Greater Manila, 1901 - 1965 - Camba, Alvin Jason A.
Situating the research in Greater Manila during the period of 1901 to 1965, the thesis argues that the process of suburbanization of Greater Manila has always been private-led, with the suburban real elites, American companies, and members of the elite society as primary movers, through their construction of subdivisions and movement into the suburbs, a process followed by the competing and chamging configurations of the private sector since the American period, and the process that started because of a confluence of urban, political, economic, education, demographic characteristics of the city during the American colonial rule and a system that was sustained in the postwar period. There were, definitely, exceptions to this private-led suiburbanization, but in those cases, the private sector still influenced these outcomes through their political and economic power. Overall, these developments led to suburban sprawl after the subdivisions were established. The thesis utilizes a nuanced version of the flight from blight and natural evolution perspective by grounding these using colonial documents and thoroughly analysis of population and census data.